2011
DOI: 10.1002/jcb.23063
|View full text |Cite
|
Sign up to set email alerts
|

The localization of hnRNP A2/B1 in nuclear matrix and the aberrant expression during the RA‐induced differentiation of human neuroblastoma SK‐N‐SH cells

Abstract: Heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 is involved in the synthesis of RNA. Its expression is up-regulated in many tumor cell lines. In this study, we investigated the distribution of hnRNP A2/B1 in the nuclear matrix, including its co-localization with expression products of related genes. Results from 2-DE PAGE and MS showed that hnRNP A2/B1 is involved with components of nuclear matrix proteins of SK-N-SH cells, and that its expression level is down-regulated after retinoic acid (RA) treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…Thus, hnRNP A2/B1 was required to maintain the undifferentiated and epithelial phenotypes of hESCs. Our findings are also supported by two recent studies in which hnRNP A2/B1 expression was decreased when undifferentiated and epithelial neuroblastoma and gastric adenocarcinoma were induced to differentiate []. However, the previous study reported that hnRNP A2/B1 knockdown is correlated with an increase of E‐cadherin expression and downregulation of E‐cadherin repressor molecules in the mesenchymal type of lung cancer cells .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, hnRNP A2/B1 was required to maintain the undifferentiated and epithelial phenotypes of hESCs. Our findings are also supported by two recent studies in which hnRNP A2/B1 expression was decreased when undifferentiated and epithelial neuroblastoma and gastric adenocarcinoma were induced to differentiate []. However, the previous study reported that hnRNP A2/B1 knockdown is correlated with an increase of E‐cadherin expression and downregulation of E‐cadherin repressor molecules in the mesenchymal type of lung cancer cells .…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies suggested that p53 may be directly associated with hnRNP A2/B1 in some cancer cell lines [], and other studies also suggested that hnRNP A2 gene itself may be a target of p53, since p53 represses the expression of hnRNP A2 mRNA . However, it seems that hnRNP A2 does not modulate p53 expression directly, because p53 mRNA and protein levels are not significantly altered in hnRNP A2 knockdown cancer cells [].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were performed as previously described [18]. Mz‐ChA‐1 cells and ESC‐3‐treated cells were seeded on a cover slip and cultured overnight.…”
Section: Methodsmentioning
confidence: 99%